Reproducción del falso vampiro lanudo Chrotopterus auritus (Chiroptera: Phyllostomidae) en un bosque tropical húmedo de la costa pacífica de Guatemala - Álvarez-Yax, Rocío A.; Gómez-Lemus, Ana H.; Hernández-Fuentes, Julia S.; Juárez-Bolaños, Andrea P.; Pérez-Quan, Katty J.; Tijerino-Escobar, Donald G.; Villatoro-Castañeda, Melissa; Ariano-Sánchez, Daniel (Instituto de Ecología, A.C., 2018)
We documented one female Chrotopterus auritus in a lactation state with her calf present in the ventral part of her body. The specimen was captured with a harp trap in a humid tropical forest of the Pacific coast of Guatemala, within private natural reserve Finca Patrocinio, Quetzaltenango, Guatemala on May 29th, 2017. There is little information about this species’ biology, especially within Guatemala, which reflects the importance of further studies on the wild behavior of this species.